Artificial Intelligence and Machine Learning for Multi-Domain Operations Applications III 2021
DOI: 10.1117/12.2586988
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient 'in memory' computing to enable decentralised service workflow composition in support of multi-domain operations

Abstract: Future Multi-Domain Operations (MDO) will require the coordination of hundreds-even thousands-of devices and component services. This will demand the capability to rapidly discover the distributed devices/services and combine them into different workflow configurations, thereby creating the applications necessary to support changing mission needs. To meet these objectives, we envision a distributed Cognitive Computing System (CCS) that consists of humans and software that work together as a 'Distributed Federa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…In the SPIE21 11 paper it was demonstrated that HVs can be used to perform IoBT service workflow orchestration in typical MDO TacCIS environments. In these environments D is limited by the capability to efficiently exchange HVs over relatively low bandwidth communications networks.…”
Section: Bsc Vs Shv Bundling Capacitymentioning
confidence: 99%
See 4 more Smart Citations
“…In the SPIE21 11 paper it was demonstrated that HVs can be used to perform IoBT service workflow orchestration in typical MDO TacCIS environments. In these environments D is limited by the capability to efficiently exchange HVs over relatively low bandwidth communications networks.…”
Section: Bsc Vs Shv Bundling Capacitymentioning
confidence: 99%
“…To demonstrate how a VSA approach can be used to perform typical MDO tasks the SPIE21 11 paper described a communications re-planning task being performed in a typical MDO TacCIS environment where agile rapid communications re-planning is required. The demonstration showed how a radios and communications plans can be represented as VSA HVs and how by exchanging the HVs over a number of radio networks, the HVs can be used to discover radio's operating under a current communications plan and instruct them to switch to a required target communications plan.…”
Section: Using Shvs and Snn Circuits In An Mdo Scenariomentioning
confidence: 99%
See 3 more Smart Citations